Role of water users in the conservation of forests on the southern slopes of Mount Kilimanjaro. Issue 3 (3rd February 2023) - Lyimo, Emmanuel H.; Kessy, Daniel; Mremi, Rudolf; Kisingo, Alex
Abstract: Mount Kilimanjaro Forest (MKF) is recognized as a major provider of hydrological services to people in northern Tanzania. However, little is understood in terms of the roles of upstream and downstream communities in protecting and conserving MKF. This article applies binomial generalized linear models to understand the role of the community in supporting the protection and conservation of MKF based on data collected through a questionnaire survey from 90 households on the southern slopes of Mount Kilimanjaro. Results showed that 99% of respondents were aware of the value of MKF as a major provider of hydrological services, however, this did not vary significantly across age groups, gender, level of education, and location (upstream vs. downstream). Further results showed that, contrary to downstream communities, upstream communities play a significant role in supporting the ecological integrity and hydrological functions of MKF by planting and protecting tree cover, joining efforts through conservation clubs, donating cash to finance its protection, and adhering to bylaws governing environmental management. Hence, adopting an approach that integrates upstream and downstream communities in managing catchment forests and ensuring the sustainable flow of hydrological services is critical. The study also has unleashed water user behavior that have enlightened demand for more studies in the area. HIGHLIGHTS: Little is known about the difference in roles played by upstream and downstream communities in protecting Mount Kilimanjaro Forest (MKF). 99% of all respondents were aware of the value of MKF as a major provider of water services. Upstream communities play a significant role in supporting the ecological integrity and hydrological function of MKF by planting and protecting tree cover, etc. Although Mt. Kilimanjaro forest offers invaluable hydrological services for livelihood, uncontrolled fires, deforestation, and climate change would trigger a water crisis. Hence, understanding the involvement and roles of communities in protecting MKF is critical for the sustainable flow of hydrological services. Further results showed that, contrary to downstream communities, upstream communities play a significant role in supporting the ecological integrity and hydrological function of MKF by planting and protecting tree cover, joining efforts through conservation clubs, donating cash to finance its protection, and adhering to bylaws governing its management. Hence, an approach that integrates upstream and downstream communities in managing catchments to ensure sustainable flow of hydrological services is critical.